PEMEKATAN EKSOPOLISAKARIDA (EPS) DARI KULTUR BAKTERI USUS DALAM BIOMASSA SAGU (Metroxylon SP.) MELALUI MODUL MEMBRAN ULTRAFILTRASI CROSS-FLOW (UFCF) - Agustine Susilowati; Aspiyanto; Achmad Dinoto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Cross-flow ultrafiltration (UF) membrane is a main separation and/or concentration techniques influenced by operation condition (flow rate, temperature, pressure, time) and molecular weight (MW). The goal of this experiment was to find out the effect of concentration time of Lactobacillus sp. FU 0811 and Enterobacter sp. FU 0813 cultures in biomass of sago (Metroxylon sp.) on UF membrane performance (flux value and rejection), and retentate/concentrate composition as carrier agent of oral insuline activated compounds. Concentration process was performed through cross-flow UF membrane module at pump motor frequency of 20 Hz (flow rate of 7.5 L/minute), room temperature and operation pressure of 5 bar for each 0, 15, 30 and 45 minutes. The result of experiment showed that retentate/concentrate had better composition and total microbes count than that permeate. Based on EPS as reduction sugar, time needed to concentrate Lactobacillus sp. FU 0811 culture as retentate/concentrate was reached at 30 minutes, with reduction sugar, total solids, total acids concentrations, and total microbes count of 4.2 mg/mL, 0.2443% and 0.013%, and 4.61 log CFU/mL. While, permeate flux value was 43.66 L/m2.hour, and rejections of reduction sugar, total solids, total microbes and total acids on membrane were 85.7–90.6%, 96.6–99.1%, 100% dan 12.9–40.2%. Whereas, EPS as reduction sugar, time needed to concentrate Enterobacter sp. FU 0813 culture as retentate/concentrate was reached at 30 minutes, with reduction sugar, total solids, total acids concentrations, and total microbes count of 0.18 mg/mL, 0.0901% and 0.013%, and 4.806 log CFU/mL. While, permeate flux value was 40.83 L/m2.hour, and rejections of reduction sugar, total solids, total microbes and total acids on membrane were 0–68.75%, 81.4–86.8%, 100%, dan 17.6 – 30.3%. Identification of retentate/concentrate from Lactobacillus sp. FU 0811 culture showed that its presence of EPS compounds as Dextran (MW 10,500 Dalton, Da.), Maltohexaose (MW 342.3 Da.) and Lactose (MW 990.86 Da.)